PENGEMBANGAN MODEL KEPEMIMPINAN KEPALA MADRASAH DALAM MENUMBUHKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU MELALUI INTERNALISASI NILAI IKHLAS, AMANAH, DAN KHIDMAH PADA MADRASAH IBTIDAIYAH SWASTA - Akhmad Nor; Mukhamad Ilyasin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Changes in the educational environment in the Society 5.0 era require educational institutions to strengthen the quality of human resources that are not only professionally competent but also demonstrate voluntary behaviors that support organizational effectiveness. In the context of Private Islamic Elementary Schools (Madrasah Ibtidaiyah Swasta—MIS), such behavior is reflected in teachers’ Organizational Citizenship Behavior (OCB), which plays an important role in improving educational quality and organizational sustainability. This study aims to develop a principal leadership model for fostering teachers’ OCB through the internalization of the values of ikhlas (sincerity), amanah (trustworthiness), and khidmah (service). The study employed a qualitative approach with a model development design through theoretical review and conceptual analysis of the literature on educational leadership, Islamic leadership, value internalization, and OCB. The findings indicate that an effective madrasah principal leadership model integrates transformational leadership, servant leadership, spiritual leadership, and prophetic leadership, which are implemented through role modeling, mentoring, empowerment, and the strengthening of organizational culture. The internalization of the values of ikhlas, amanah, and khidmah serves as the primary mechanism for shaping teachers’ OCB, including willingness to assist colleagues, active participation in madrasah activities, organizational loyalty, and readiness to perform tasks beyond formal responsibilities. This study proposes a value-based leadership model that positions value internalization as the linking mechanism between madrasah principal leadership and the development of teachers’ OCB. The findings contribute to the advancement of Islamic educational leadership theory and provide practical guidance for madrasah principals and policymakers in enhancing educational quality in a sustainable manner.